Spatiotemporal analysis of zebrafish hox gene regulation by Cdx4. Issue 12 (30th September 2015) - Hayward, Albert G.; Joshi, Piyush; Skromne, Isaac
Abstract : Background: Cdx factors expressed in caudal regions of vertebrate embryos regulate hox patterning gene transcription. While loss of Cdx function is known to shift hox spatial expression domains posteriorly, the mechanism underlying the shift is not understood. We addressed this problem by analyzing the spatiotemporal expression profile of all 49 zebrafish hox genes in wild‐type and Cdx4‐deficient embryos.Results: Loss of Cdx4 had distinct effects on hox spatial expression in a paralogous group‐dependent manner: in the head, group 4 expression was expanded posteriorly; in the trunk, group 5–10 expression was shifted posteriorly; and in the tail, group 11–13 genes were expressed in the tail bud but not in more differentiated tissues. In the trunk neural tissue, loss of Cdx4 severely delayed both transcriptional activation of hox genes during the initiation phase, and the anterior‐ward expansion of hox expression domains during the establishment phase. In contrast, in the trunk mesoderm, loss of Cdx4 only delayed the hox initiation phase.Conclusions: These results indicate that Cdx4 differentially regulates the transcription of head, trunk and tail hox genes. In the trunk, Cdx4 conveys spatial positional information to axial tissues primarily by regulating the time of hox gene transcriptional activation during the initiation phase. Developmental Dynamics 244:1564–1573, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: Zebrafish hox genes, as their mouse homologues, are transcribed in three phases: initiation, establishment and maintenance. Cdx4 differentially regulates the spatial expression domains of head (hox1‐4), trunk (hox5‐10) and tail (hox11‐13) hox genes. Cdx4 regulates the timing of hox5‐10 induction in neural and mesodermal tissues during the initiation phase. Cdx4 regulates the anterior‐ward expansion of hox5‐10 expression domains in the neuroectoderm during the establishment phase. Cdx4 is not necessary for hox5‐10 regulation during the maintenance phase.